2017
DOI: 10.1016/j.kint.2017.01.014
|View full text |Cite
|
Sign up to set email alerts
|

Vascular adhesion protein-1 enhances neutrophil infiltration by generation of hydrogen peroxide in renal ischemia/reperfusion injury

Abstract: Vascular adhesion protein-1 (VAP-1) is a unique molecule since it acts as an adhesion molecule as well as an ectoenzyme catalyzing oxidative deamination of primary amines and generates hydrogen peroxide in the extracellular space. While VAP-1 is implicated in various inflammatory diseases, its role in acute kidney injury is less characterized. Here we studied VAP-1 expression in the kidney and the effect of its inhibition in a rat model of renal ischemia/reperfusion injury. VAP-1 was predominantly expressed in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(50 citation statements)
references
References 51 publications
(62 reference statements)
0
47
1
2
Order By: Relevance
“…16,91,[146][147][148][149][150] Inhibition of neutrophil recruitment reduces organ injury in many animal models. [151][152][153][154][155][156][157][158] Data suggest that release of granule cargo and ROS generation mediate neutrophil-dependent organ damage. 154,159,160 A role for ROS is supported by finding oxidant-modified proteins in organs damaged by ischemia-reperfusion injury.…”
Section: Sepsis and Ischemia-reperfusion Injurymentioning
confidence: 99%
“…16,91,[146][147][148][149][150] Inhibition of neutrophil recruitment reduces organ injury in many animal models. [151][152][153][154][155][156][157][158] Data suggest that release of granule cargo and ROS generation mediate neutrophil-dependent organ damage. 154,159,160 A role for ROS is supported by finding oxidant-modified proteins in organs damaged by ischemia-reperfusion injury.…”
Section: Sepsis and Ischemia-reperfusion Injurymentioning
confidence: 99%
“…However, discordant results led to questioning of the role of neutrophils during early AKI pathogenesis [2]. Recent studies, however, have shown that blocking neutrophil infiltration by inhibition of vascular adhesion protein-1 or leukotriene B4-leukotriene B4 receptor axis had protective effect against ischemia-reperfusion injury (IRI) and cisplatin-induced AKI, respectively [3,4]. …”
Section: Immune Cells In Akimentioning
confidence: 99%
“…VAP-1 is expressed predominantly in pericytes, which release enzymatically active VAP-1. Inhibition of VAP-1 decreased neutrophil infiltration and ameliorated renal ischemia-reperfusion injury in rats [6]. We also found that CCAAT/enhancer-binding protein δ (CEBPD), a transcription factor and inflammatory response gene, is a novel regulator of HIF-1, a master regulator of defensive mechanisms against hypoxia.…”
Section: Introductionmentioning
confidence: 70%